2020
DOI: 10.3390/jcm9103195
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus and Human Adenovirus Viremia in Renal Tumors Is Associated with Histological Features of Malignancy

Abstract: Background: There is growing evidence that viral infections may impact the risk and clinical course of malignancies, including solid tumors. The aim of this study was to assess the possible association of selected chronic/latent viral infections with the clinical course of renal cell carcinoma (RCC). Methods: In this prospective study we enrolled 27 patients undergoing partial or radical nephrectomy due to the histologically confirmed RCC and followed them up for one year post-operation. Isolation of the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…Moreover, we found the viral transcription and viral gene expression pathways were upregulated in subtype 3 and downregulated in subtype 2, suggesting that these two subtypes' molecular characteristics may be associated with virus infection. It has been reported that the infection of hepatitis C virus, Epstein-Barr virus and human adenovirus viremia is associated with the development of kidney cancer ( Hofmann et al., 2011 ; Kryst et al., 2020 ; Wu et al., 2021 ). The downregulated genes in subtype 3 were significantly enriched in fatty acid metabolism-related pathways such as fatty acid catabolic procession and fatty acid oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found the viral transcription and viral gene expression pathways were upregulated in subtype 3 and downregulated in subtype 2, suggesting that these two subtypes' molecular characteristics may be associated with virus infection. It has been reported that the infection of hepatitis C virus, Epstein-Barr virus and human adenovirus viremia is associated with the development of kidney cancer ( Hofmann et al., 2011 ; Kryst et al., 2020 ; Wu et al., 2021 ). The downregulated genes in subtype 3 were significantly enriched in fatty acid metabolism-related pathways such as fatty acid catabolic procession and fatty acid oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The upregulated genes in subtype 3 were significantly enriched in the translational initiation and protein localization to ER pathways, which showed an opposite character to subtype 2 (Figure 3E). Moreover, we found the viral transcription and viral gene expression pathways were upregulated in subtype 3 and downregulated in subtype 2, suggesting that these two subtypes' molecular characteristics (Hofmann et al, 2011;Kryst et al, 2020;Wu et al, 2021). The downregulated genes in subtype 3 were significantly enriched in fatty acid metabolism-related pathways such as fatty acid catabolic procession and fatty acid oxidation.…”
Section: Clinical and Molecular Characteristics Of Subtypesmentioning
confidence: 87%
“…This finding is in line with a study by Shimakage et al on 9 RCC cases and 2 RCC cell lines, all of which were found to be infected with EBV [ 12 ]. The frequency of EBV infection in RCC tumors was reported to be 15.6% and 29.6% in two other former studies [ 13 , 14 ]. Our results, along with the others’, show that EBV infection is common in RCCs.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the expression of EBV nuclear antigen 2 (EBNA2) in renal tubule cells has been reported to induce renal tumors in transgenic mice [ 11 ]. Furthermore, there are accumulating data available suggesting a role for EBV in RCC pathogenesis [ 12 14 ]. Together, these findings not only suggest that renal tissue is a likely reservoir of EBV, but also imply the oncogenic potential of EBV in the renal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The method was previously described. 14 Viral nucleic acids were isolated from plasma using EZ1 Virus Mini Kit v2.0 (Qiagen, Hilden, Germany) according to the manufacturer's instructions with a BioRobot EZ1 device (Qiagen, Hilden, Germany). Quality and quantity control was done using an ND-1000 spectrophotometer (NanoDrop Technologies, Wilmington, Delaware, USA).…”
Section: Methodsmentioning
confidence: 99%